Therapeutic Potentials of Synapses after Traumatic Brain Injury: A Comprehensive Review - Zunjia Wen; Dong Li; Meifen Shen; Gang Chen (Neural Plasticity)
Massive studies have focused on the understanding of the pathobiology of cellular and molecular changes and injury mechanisms after traumatic brain injury (TBI), but very few studies have specially discussed the role of synapses in the context of TBI. This paper specifically highlights the role and therapeutic potentials of synapses after TBI. First, we review and conclude how synapses interact with constant structural, metabolic, neuroendocrine, and inflammatory mechanisms after TBI. Second, we briefly describe several key synaptic proteins involved in neuroplasticity, which may be novel neuronal targets for specific intervention. Third, we address therapeutic interventions in association with synapses after TBI. Finally, we concisely discuss the study gaps in the synapses after TBI, in hopes that this would provide more insights for future studies. Synapses play an important role in TBI; while the understandings on the synaptic participation in the treatments and prognosis of TBI are lacking, more studies in this area are warranted.